The effect of protean careers on talent retention: examining the relationship between protean career orientation, organizational commitment, job satisfaction and intention to quit for talented workers. Issue 9 (15th May 2021) - Redondo, Raquel; Sparrow, Paul; Hernández-Lechuga, Gabriela
Abstract: To study the effect of protean careers on talent retention, operationalized as the intention to quit, this study explores two pathways between protean career orientation and intention to quit: a direct pathway, and an indirect pathway via organizational commitment and job satisfaction. The study draws upon a sample of 306 talented workers selected from 17 Spanish and Mexican multinational organizations. Protean orientation should be expected to be widespread among talented individuals which might represent a threat to those that seek to develop and retain highly valued employees. We found that highly protean talented individuals show higher organizational commitment and higher job satisfaction, but contrary to expectations do not show a higher intention to quit. The total effect of protean career orientation on intention to quit is shown to not be significant because the positive direct effects are neutralized by negative indirect effects. The results help complement current knowledge of protean careers and a better understanding of organizational attitudes in the protean career context will help practitioners to show the importance of avoiding stereotyping talented employees based on a protean orientation as they do not comprise an extra risk for the organization in terms of commitment and turnover intention.